Morphological and Cytogenetic Responses of In Vitro-Grown Grapevine (Vitis vinifera L.) Plants from “Touriga Franca”, “Touriga Nacional” and “Viosinho” Varieties Under Water Stress - Ana Carvalho; Christina Crisóstomo; Fernanda Leal; José Lima-Brito (Stresses, 2024)
According to the climate projections, drought will increase in frequency and severity. Since water stress (WS) impacts a grapevine’s physiology and yield negatively, the evaluation and selection of tolerant genotypes are needed. To analyse the WS effects on the morphology and cell division of three grapevines (Vitis vinifera L.) varieties, “Touriga Franca” (TF), “Touriga Nacional” (TN) and “Viosinho” (VS), in vitro-grown plants were exposed to 10% polyethylene glycol 6000 (PEG) (−0.4 MPa) or 20% PEG (−0.8 MPa), incorporated in the culture medium, for four weeks. Control plants were kept in culture media without PEG. The VS and TN plants showed the highest mean numbers of nodes, shoots and leaves and average mitotic indexes under 20% PEG. The TF and TN plants showed the lowest frequencies of mitotic anomalies under 10% PEG. The VS plant growth was less affected by WS, but TF and TN presented more regular mitosis under moderate WS. Globally, in vitro culture constitutes a cost-effective experimental system for studying grapevine responses to WS and the preliminary selection of resilient genotypes. These approaches could be applied to study plant responses to other abiotic stresses based on additional evaluation techniques (e.g., transcriptional analyses or genome-wide association studies).